2023
DOI: 10.1177/17455057231184507
|View full text |Cite
|
Sign up to set email alerts
|

Time-out for well-being: A mixed methods evaluation of attitudes and likelihood to engage in different types of online emotional well-being programmes in the perinatal period

Abstract: Background: Positive maternal mental health during the perinatal period contributes to general well-being and positive emotional bonds with the child, encouraging an optimal developmental trajectory. Online interventions to enhance maternal well-being and develop coping skills, such as meditation-based interventions, can be a low-cost way to improve mother and child outcomes. However, this depends on end-user engagement. To date, there is limited evidence about women’s willingness to engage and preferences for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Future intervention design approaches should consider making an intervention as minimal and as engaging as possible to achieve the desired result (ie, decrease time commitment). In our previous study, pregnant women indicated their preferences for these types of interventions of <4 modules per week, <15 minutes in duration, delivered over a 4-week period [ 36 ]. In addition, future consideration should be given to women being provided guidance by health care providers to find prioritized or dedicated time as part of their prenatal self-care.…”
Section: Discussionmentioning
confidence: 99%
“…Future intervention design approaches should consider making an intervention as minimal and as engaging as possible to achieve the desired result (ie, decrease time commitment). In our previous study, pregnant women indicated their preferences for these types of interventions of <4 modules per week, <15 minutes in duration, delivered over a 4-week period [ 36 ]. In addition, future consideration should be given to women being provided guidance by health care providers to find prioritized or dedicated time as part of their prenatal self-care.…”
Section: Discussionmentioning
confidence: 99%